2013
DOI: 10.1590/s0103-21002013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Carga de trabalho de enfermagem em unidade de recuperação pós-anestésica

Abstract: Objectives: To assess nursing workload in the post-anesthesia care unit and its potential correlations with a surgical severity index, length of stay, magnitude of surgery, and patient age. Methods: Cross-sectional study conducted at a university hospital. Workload was assessed by the Nursing Activities Score, and severity of illness, by the Simplified Acute Physiology Score II. Both were assessed at the time of discharge from the unit. Results: The study sample comprised 160 patients (mean age, 57 ± 15 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
19

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 9 publications
2
14
0
19
Order By: Relevance
“…This instrument has detected high nursing workloads in general and specialized intensive care units (ICU), with median scores ranging from 66.6% to 74,4% (5,(9)(10) . The NAS is also applicable to units with highly care-dependent patients (11) , individuals with longer postanesthetic recovery periods (12) and to specialized inpatient units (13)(14) . Although the assessment of nursing workload using the NAS could make signifi cant contributions to both the literature and clinical practice, a brief review of the literature revealed that most studies using this instrument focused on general ICUs and, in cardiology studies, only in postoperative heart surgery patients (8,10,15) .…”
Section: Introductionmentioning
confidence: 99%
“…This instrument has detected high nursing workloads in general and specialized intensive care units (ICU), with median scores ranging from 66.6% to 74,4% (5,(9)(10) . The NAS is also applicable to units with highly care-dependent patients (11) , individuals with longer postanesthetic recovery periods (12) and to specialized inpatient units (13)(14) . Although the assessment of nursing workload using the NAS could make signifi cant contributions to both the literature and clinical practice, a brief review of the literature revealed that most studies using this instrument focused on general ICUs and, in cardiology studies, only in postoperative heart surgery patients (8,10,15) .…”
Section: Introductionmentioning
confidence: 99%
“…(1) The IADIC was able to show pain in the association between the presence of pain and levels of complexity of the surgical procedures (p = 0.020), showing that the patients in this study that underwent high-complexity procedures had more pain than those who underwent low / medium complexity procedures, this result has also been found in other studies. (1,18,19) A survey conducted in inpatient units of a general hospital, where pain and satisfaction with analgesia was evaluated in 110 adult patients, found that 97.6% of patients who underwent major surgery reported pain, where 38.7% described the pain as severe, between 8 and 10 when evaluated by the numerical pain scale. (19)…”
Section: Discussionmentioning
confidence: 99%
“…(1,18,19) A survey conducted in inpatient units of a general hospital, where pain and satisfaction with analgesia was evaluated in 110 adult patients, found that 97.6% of patients who underwent major surgery reported pain, where 38.7% described the pain as severe, between 8 and 10 when evaluated by the numerical pain scale. (19)…”
Section: Discussionmentioning
confidence: 99%
“…Patients were selected based on the operating room surgical schedule. The sample included adult patients who underwent elective surgical procedures requiring anaesthesia, classified as surgical class 2, 3 or 4 (Lima & Rabelo, 2013). Briefly, surgical class is dependent on operative time, with class one (1) corresponding to surgical procedures lasting up to 2 hr, class two (2) to procedures lasting 2 hr 1 min to 4 hr, class three (3) to procedures lasting 4 hr 1 min to 6 hr, and class four (4) to procedures lasting 6 hr and 1 min or longer (Lima & Rabelo, 2013).…”
Section: Participantsmentioning
confidence: 99%
“…The sample included adult patients who underwent elective surgical procedures requiring anaesthesia, classified as surgical class 2, 3 or 4 (Lima & Rabelo, 2013). Briefly, surgical class is dependent on operative time, with class one (1) corresponding to surgical procedures lasting up to 2 hr, class two (2) to procedures lasting 2 hr 1 min to 4 hr, class three (3) to procedures lasting 4 hr 1 min to 6 hr, and class four (4) to procedures lasting 6 hr and 1 min or longer (Lima & Rabelo, 2013). Surgical class was used as a criterion for patient inclusion based on a previous study that found operative time >2 hr to be a risk factor for perioperative positioning injury (Lopes & Galvão, 2010;Scarlatti et al, 2011).…”
Section: Participantsmentioning
confidence: 99%